2001
DOI: 10.1161/01.str.32.7.1607
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Paracetamol (Acetaminophen) on Body Temperature in Acute Ischemic Stroke

Abstract: on Behalf of the PAPAS InvestigatorsBackground and Purpose-Body temperature is a strong predictor of outcome in acute stroke. However, it is unknown whether antipyretic treatment leads to early and clinically worthwhile reduction of body temperature in patients with acute stroke, especially when they have no fever. The main purpose of this trial was to study whether early treatment of acute ischemic stroke patients with acetaminophen (paracetamol) reduces body temperature. Methods-Seventy-five patients with ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
52
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(57 citation statements)
references
References 31 publications
2
52
0
3
Order By: Relevance
“…In this observational study, 51% of patients taking these drugs had a good outcome compared with 38% of those not taking statins (83). Another study (18) included patients with stroke of which 18% were using statins when admitted. Better prognosis at 3 months was significantly more frequent in the statin group, indicating that these drugs may provide benefits for the long-term functional outcome when administered before the onset of cerebral ischemia.…”
Section: Other Treatmentsmentioning
confidence: 98%
See 1 more Smart Citation
“…In this observational study, 51% of patients taking these drugs had a good outcome compared with 38% of those not taking statins (83). Another study (18) included patients with stroke of which 18% were using statins when admitted. Better prognosis at 3 months was significantly more frequent in the statin group, indicating that these drugs may provide benefits for the long-term functional outcome when administered before the onset of cerebral ischemia.…”
Section: Other Treatmentsmentioning
confidence: 98%
“…New surface cooling devices, such as energy-transferring skin pads (48), may demonstrate a reduction in the time to target temperature and allow better temperature control. In a pilot trial (17), treatment with paracetamol at 6 grams daily, compared with placebo, led to a 0.3 ºC reduction in body temperature in normothermic patients. This temperature reduction is of potential but unproven clinical benefit.…”
Section: Other Treatmentsmentioning
confidence: 99%
“…The harmful effects of fever have been attributed to increased metabolic demands, changes in permeability of the blood-brain barrier, acidosis and an increased release of neurotransmitters [73,78]. Studies using animal models of focal and global ischemia have demonstrated that cerebral hyperthermia (over 39°C) can lead to larger infarct volume and more severe histological outcome [73,[79][80][81].…”
mentioning
confidence: 99%
“…17 Two randomized trials have evaluated acetaminophen in stroke patients and reported small decreases in core body temperature even in normothermic patients. 18,19 Acetaminophen may modestly promote hypothermia < 36.5°C or prevent hyperthermia > 37.5°C. 15 Unfortunately, the clinical significance of this effect appears small.…”
mentioning
confidence: 99%
“…Multiple techniques of hypothermia induction have been published including: application of ice packs; 5 surface cooling with cooled forced-air, 4,20 or circulating water blankets; 18,19 infusion of 4°C iv fluids; [26][27][28] immersion in cold water; 29 specialized endovascular cooling devices; 21,30,31 and cardiopulmonary bypass. 32 No trials comparing hypothermia techniques in cardiac arrest patients have been published.…”
mentioning
confidence: 99%